Exploring Teacher Educators’ Self-Assessment of AI-Assisted Writing:: A Case Study in Eastern Indonesian Universities - Suciwati, Ika; Kholidi, Muh. Azhar; Ramadhani, Suciaty; Anggeraini, Nining; Rofikah, Ummu; Pardani, Sulastri (International Journal of Language Teaching and Education, 2026)
This study attempts to explore how English as a Foreign Language (EFL) teacher educators perceive the impact of artificial intelligence (AI)-assisted writing on their academic writing practices, with a focus on self-assessment. Using a qualitative case study, semi-structured interviews were conducted with six early-career lecturers from universities in Eastern Indonesia who actively use AI-assisted writing tools such as ChatGPT, Grammarly, and QuillBot. The findings show that AI enhances linguistic accuracy, coherence, writing efficiency, and confidence by providing immediate feedback and supporting independent revision. At the same time, participants expressed concerns about overreliance, creativity loss, and authorship, leading them to regulate AI use critically and reflectively. The findings also highlight contextual challenges related to institutional support, digital infrastructure, and unequal access to AI resources, alongside expectations for more integrated AI applications. This study contributes to the growing literature by extending the discussion beyond AI adoption to teachers' self-assessment, explaining how AI builds writing confidence through greater writing autonomy, and providing qualitative evidence from the underexplored context of Eastern Indonesia. The findings offer practical implications for teacher professional development and the responsible integration of AI in higher education.